Association of Matrix Metalloproteinase-9 Gene -1562C/T Polymorphism with Essential Hypertension: A Systematic Review and Meta-Analysis Article - Wenchao YANG; Jiaojiao LU; Liu YANG; Jinjin ZHANG (Tehran University of Medical Sciences, 2015)
Background: Matrix metalloproteinase-9 (MMP-9) gene -1562C/T polymorphism could regulate its expression level and thus affected people's predisposition to essential hypertension. However, related studies yielded inconsistent or contradictory results. Methods: To evaluate the association of MMP-9 -1562C/T polymorphism with essential hypertension, we performed a meta-analysis by combining all available independent case-control studies (n=6).A systematic literature search of PubMed, Web of Science, Scopus and CNKI (Chinese National Knowledge Infrastructure) databases was conducted by two researchers independently for all relevant articles published before March 2015. Results: MMP-9 -1562C/T polymorphism was associated with essential hypertension under the allelic model (T vs.C, OR=1.36, 95% CI=1.17-1.59, P<0.0001). Subsequent sensitivity analysis confirmed the stability of the results. Such association was also observed in the dominant (TT+CT vs. CC, OR=1.30, 95% CI=1.10-1.54, P=0.002) and co-dominant (CT vs. TT+CC, OR=1.27, 95% CI=1.05-1.53, P=0.01) models but not in the recessive model (TT vs. CT+CC, OR=1.30, 95% CI=0.50-3.36, P=0.59). Conclusion: MMP-9 -1562C/T polymorphism was associated with the risk of essential hypertension.   Keywords: MMP-9, Essential hypertension, Meta-analysis